DEVELOPING ANIMATION VIDEOS AS LEARNING MEDIA FOR STUDENTS SPEAKING ABILITY IN DESCRIPTION TEXT ON JUNIOR HIGH SCHOOL 2 METRO - Nurul Fitri; Syaifudin Latif Darmawan; Bambang Eko Siagiyanto (Universitas Muhammadiyah Metro, 2022)
Animation has many benefits such as clearer and attractivelearning, the learning process is more efficient, effective because students canrepeat it as needed, can improve the quality of learning outcomes, and can overcomethe limitations of space and time between teachers and student.This study of learningmedia in the form of animated videos will be very helpful for teachers and students asan attractive learning media and make it easier for students to learn and understandEnglish subjects, especially in speaking skill on descriptive text material. The type ofthis research are research and development (R&D). The models of this research areADDIE model. There are five steps in ADDIE model; analysis, design, development,implementation, and evaluation. Assessment on video animation by media expertsand material experts gets a percentage 79% and 82%. Students and teachers gave apositive assessment that is 82% and 96%, each assessment was in the very goodcategory.